MONITORING OF THE PSYCHOPHYSICAL CONDITION OF STUDENTS STUDYING IN THE SPECIALTY 017 PHYSICAL CULTURE AND SPORT (Physical Culture and Sport: Scientific Perspective, 2024)
Taking into account the fact that in the modern conditions of the educational and training process of physical education and sports specialists, more and more time is devoted to online learning, the relevance of the development of interoceptive awareness only increases. Somatic classes are held both face-to-face and offline. The number of applicants depends on the qualifications of the teacher and the capacity of the audience. 1-3 academic groups can be present at one intramural somatic lesson. The number of participants in somatic online classes depends only on the software, i.e. much more (for example, for communication in the "Zoom" program, there can be up to 500 listeners).The purpose of the study is to evaluate the "Not-Worrying" (the third domain of interoceptive awareness, MAIA-2ukr) of 1st-year students of the Faculty of Health, Physical Education and Sports of the Borys Grinchenko Kyiv metropolitan University. Material and methods — the scientific and methodological literature and available Internet sources on the chosen topic were analyzed in detail, as well as the indicators of the third domain of the MAIA-2ukr scale were evaluated and statistically worked out. 50 first-year students of the Faculty of Health, Physical Education and Sports participated in the study. As a result, new indicators of the Not-Worrying subscale, which assesses the tendency not to worry or not to experience emotional stress when experiencing pain or discomfort, were obtained for 1st-year students of the Faculty of Health, Physical Education and Sports of Borys Grinchenko Kyiv University, necessary for further analysis and synthesis of indicators of interoceptive awareness of higher education students of the first (bachelor) level. The obtained data indicate that a significant number of students - 22% are always upset when they feel physical pain; 24% quite often begin to worry that something is wrong if they feel any discomfort; 26%, noticing discomfort in their body, rarely worry about it; 28% can quite often keep calm and not worry when they feel discomfort or pain; 26%, experiencing discomfort or pain, quite rarely do not worry about it. Therefore, the process of preparing for physical education lessons needs corrections in view of the obtained indicators of the Not-Worrying subscale.
Keywords: nts of higher education of the first (bachelor) level; interoceptive awareness; the process of physical education; somatic lessons